2006
DOI: 10.1179/146531205225021615
|View full text |Cite
|
Sign up to set email alerts
|

A clinical comparison of bracket bond failures in association with direct and indirect bonding

Abstract: There was no significant difference in the bond failure rates between direct and indirect bonding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 19 publications
4
29
0
6
Order By: Relevance
“…Most studies report significant differences in the SBS of directly and indirectly bonded systems. Some exceptions include Thiyagarajah et al 40) , who compared the clinical performance of the direct and indirect techniques, as well as Linn et al 9) and Daub et al 41) , who observed no significant differences in the SBS of the two techniques. Comparisons should be interpreted carefully and with discernment by the reader, as most of the previous studies related to indirect bonding 9,40,41) have investigated different techniques of bonding procedures with two different types of materials, such as light-cured and chemically cured, but these materials require the application of a conditioner agent such 37% phosphoric acid 21) , , which have showed higher mean values of SBS than the self-etching system 34,35) that has been analyzed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies report significant differences in the SBS of directly and indirectly bonded systems. Some exceptions include Thiyagarajah et al 40) , who compared the clinical performance of the direct and indirect techniques, as well as Linn et al 9) and Daub et al 41) , who observed no significant differences in the SBS of the two techniques. Comparisons should be interpreted carefully and with discernment by the reader, as most of the previous studies related to indirect bonding 9,40,41) have investigated different techniques of bonding procedures with two different types of materials, such as light-cured and chemically cured, but these materials require the application of a conditioner agent such 37% phosphoric acid 21) , , which have showed higher mean values of SBS than the self-etching system 34,35) that has been analyzed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Çeşitli araştırmalarda, hem indirekt hem de direkt teknikte braketlerin dişler üzerinde en doğru konumda pozisyonlandırılabilmesinin mümkün olabildiği belirtilmiştir. [17][18][19][20][21] Hekime bağlı yorgunluk, yoğunluk faktörlerinin braketlerin doğru konumda yapıştırılmasına etki edebilmesi mümkün görülmektedir. Bu durum, tedavi süresininın uzamasına ve sonuçta hasta hayat kalitesinin düşmesine neden olabilmektedir.…”
Section: Bulgularunclassified
“…Thiyagarajah et al (46) used light-cured resin (Transbond XT) for both direct and indirect bonding. Thirty-three patients were included in the study and were followed up for 1 year.…”
Section: In Vivo Studies Of the Indirect Bonding Techniquementioning
confidence: 99%